Nonstandard wh-Questions: Focusing on Bulgarian wh-li Questions - Margarita Dimitrova (Studi Slavistici, 2025)
This paper examines nonstandard wh-questions in Bulgarian, with a focus on wh-li constructions, in which the wh-constituent co-occurs with the interrogative particle li. The distribution of li in Bulgarian interrogatives has been widely discussed, as its behavior in yes-no and wh-questions reveals intriguing asymmetries. While in wh-questions li conveys a strong sense of wondering or doubt, in yes-no questions the particle is crucial to the interrogative interpretation – its absence yielding a presuppositional reading. In light of these contrasts, we propose that particles like li are related to quantification and the presence of alternative sets. Based on this property, we argue that the appearance of li in wh-questions triggers semantic mechanisms such as domain extension. Additionally, drawing on prior analyses of non-canonical questions in Romance languages, we suggest that the licensing of nonstandard wh-li questions involves structurally higher projections within the Left Periphery.